Mental health for the indigenous population in Chhattisgarh, India: Navigating challenges and crafting solutions - Monika Thakur; Namrata Bhardwaj; Hari Hara Suchandra; R Arun Kumar; K Pushpa; Nisha R. Harshitha; Suhas Satish; Sumi Jain; Radhakrishnan Govindan; Narayana Manjunatha; Channaveerachari Naveen Kumar; Suresh Bada Math (Journal of Family Medicine and Primary Care)
Introduction: The ST population, residing in isolated, underdeveloped areas, faces significant health disparities compared to non-tribal communities. In particular, the lack of mental health infrastructure in these regions exacerbates their health challenges. Tribal communities possess distinct cultural beliefs surrounding health and illness, yet scant information exists regarding their physical and mental well-being. In addition, limited access to mental health services prevails, and many tribal individuals opt for traditional healing methods. Methodology: This study is part of the “Tele-mentoring for Rural Health Organizers of Chhattisgarh (TORENT)” project, which aims to equip rural health organizers and community health officers (CHOs) with training to screen, identify, counsel, refer, and follow up with community members facing mental health issues. Results: Covering 27 districts in Chhattisgarh, this study enlisted trained CHOs to employ the MERIT tool for mental health screenings. Among the tribal population, the study unveiled elevated rates of tobacco and alcohol use, anxiety, depression, hallucinations, and substance use disorders. Challenges in seeking professional help were widespread, driven by transportation difficulties and limited awareness. Field visits (77%) played a pivotal role in identifying cases, alongside self-referrals and referrals by Mitanin or ASHA workers. Notably, a significant proportion had a family history of alcohol use, with a preference for a locally brewed liquor called Mahua. Discussion: This study provides vital insights into the mental health status of Chhattisgarh’s tribal populations. It underscores their socioeconomic challenges, high prevalence of substance use disorders, and barriers to accessing mental health services. The study highlights the importance of delivering mental health care within tribal communities, emphasizing the engagement of locally available primary care health workers. Furthermore, it advocates for an integrated approach that acknowledges the role of faith healers in tribal communities’ mental health care.